Heterosis, Combining Ability and Yield Prediction in Hybrids From Local Maize Inbred Lines - Sujiprihati, Sriani (1996)
Studies were conducted to identify and select for superior maize inbred lines based on their performance per 5e, and to evaluate their performance and combining ability in all possible crosses. Performance and heterosis of the single crosses were evaluated at two locations, in Universiti Pertanian Malaysia, Serdang. Furthermore, some promising double cross hybrids developed from the potential single crosses were also evaluated for performance and for comparison with the predicted. In general , most of the inbred lines exhibited poor performances due to inbreeding effects after successive generations of selfing, but some were however, found to have high potential for use in hybrid production. Hy-58, Hy-59 and Hy-60 were identified as the best performing F1 single-cross hybrids at both locations, with grain yields of 3703.7 kg/ha, 3940.7 kg/ha and 3451.9 kg/ha, respectively, at Field 2; 5659.3 kg/ha, 572 5.9 kg/ha and 5948.1 kg/ha, respectively, at Share Farm; and 468 1.5 kg/ha, 4833.3 kg/ha and 4700.0 kg/ha, respectively, in the locations combined. In general, hybrids that produced high yields were those formed between inbred parents that were themselves high yielding and from genetically diverse population sources. High heterosis was shown by grain yield, ear weight and grain weight per ear, moderate heterosis by number of kernels per row, ear height, plant height and ear length, while low heterosis was shown by ear diameter, number of kernel rows per ear, 100-grain weight and shelling percentage. Maturity characters showed negative heterosis, indicating earliness of the hybrids.